Robust production of 2D quantum sheets from bulk layered materials. Issue 7 (21st May 2019) - Xu, Yuanqing; Chen, Shulin; Dou, Zhipeng; Ma, Yanhong; Mi, Yang; Du, Wenna; Liu, Yin; Zhang, Jianqi; Chang, Jinquan; Liang, Cheng; Zhou, Jin; Guo, Hongbo; et al.
Abstract : Facile and mass production of intrinsic and defect-free 2D QSs from bulk layered materials is achieved via a unified top-down method. Abstract : The production of two-dimensional quantum sheets (2D QSs) from bulk layered materials is highly desired but far from satisfactory. Herein, we report a unified top-down method capable of producing a range of 2D QSs in high yields. The method combines silica-assisted ball-milling and sonication-assisted solvent exfoliation and thus enables production of graphene QSs (GQSs), boron nitride QSs (BNQSs), molybdenum disulfide QSs (MoS2 QSs), and tungsten disulfide QSs (WS2 QSs) in exceedingly high yields of 35.5, 33.6, 30.2, and 28.2 wt%, respectively. The as-produced 2D QSs are confirmed as intrinsic and defect-free by multiple characterization techniques. Such 2D QSs can be collected as powders and then redispersed in a wide range of solvents with high concentration up to 5 mg mL −1 . Both (re)dispersions and solid thin films of the 2D QSs exhibit extraordinarily high performance in linear and nonlinear optics. Specifically, the QS (re)dispersions show prominent exciton-, solvent-, and concentration-dependent photoluminescence, while the QS solid thin films demonstrate exciting solid-state fluorescence (with lifetimes up to 3.0 ns) and remarkable nonlinear absorption saturation (with absolute modulation depths up to 59% and saturation intensities down to 6.70 kW cm −2 (0.67 nJ cm −2 )). Our method could be applicable to any bulk layered materials and therefore paves the way for mass production and full exploration of 2D QSs.